Problem-based Learning using Scribblenauts Unlimited for Teaching English at Vocational High School - Kusuma, Desak Anugrah Dwi; Padmadewi, Ni Nyoman; Saputra, I Nyoman Pasek Hadi (Universitas Pendidikan Ganesha, 2024)
In Indonesian public schools, English is taught and studied solely as a foreign language. This has an impact on the lack of students' English skills so that appropriate learning strategies and media are needed. This study aims to analyze the significant effect of implementing PBL with the Maastricht seven-step model using the Scribblenauts Unlimited video game on the English learning achievement of grade XI students. This study uses a quantitative research method with a pre-experimental design, interviews, and surveys. The sample of this study was 27 grade 11 students and an English teacher of grade XI. Data collection was carried out through a pretest-posttest containing 20 multiple-choice questions and 5 essay questions as well as a questionnaire and interview. The data obtained were analyzed descriptively and inferentially. The results of the paired sample t-test showed that the average score after being taught using the Scribblenauts Unlimited video game (Me = 64.67) was higher than before being taught using this game (Me = 51.92) with a large Cohen's d effect size (1.35> 0.80). The students were happy to learn English. The English teachers’ opinions were positive and strongly supported the implementation of PBL using the Scribblenauts Unlimited video game in English classes at vocational schools.